Hafidh Nur Fauzi STRATEGY FOR IMPROVING QUR’AN LITERATION CULTURE IN DIGITAL ERA - Fauzi, Hafidh Nur (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2019)
In modernization, students' interest in reading the Qur'an is very alarming. At present, they spend more time playing gadgets or games than reading the Qur'an. Though reading the Qur'an is one of the keys to be a good Muslim. The ability to read and understand the Qur'an can increase insight and knowledge. This study aims to determine the school's efforts to improve the culture of literacy and Qur?an reading at Karangsari State Elementary School through extracurricular activities in collaboration with the Coordinating Board for the Qur?an Learning Center. Supporting factors in improving reading culture include support and motivation from parents and schools, while the inhibiting factor is the development of the teaching ability of educators.